Influence of the Base Element on the Thermal Properties of Non- Ferrous Chromium-Rich TaC-Containing Alloys Elaborated by Conventional Casting: Part 1: Thermodynamic Approach, Melting Ranges, as-Cast Microstructures and Thermal Expansion (Journal of Material Science and Technology Research, 2019)
After preliminary thermodynamic calculations for verifying their refractoriness, six (Ni,Co)-based alloys were synthesized by casting. They contain chromium, carbon and tantalum to achieve interesting chemical and mechanical high temperature properties. Their microstructures in the as-cast state were observed by electron microscopy (SEM) to discover the carbides characteristics. Differential thermal analysis (DTA) was carried out for all of them to assess their melting points notably, for having better knowledge about the level of high temperature at which they can be used potentially. Thereafter thermomechanical analyses (TMA) were run to explore their behaviour in thermal expansion. As shown by the thermodynamic calculations all the alloys are theoretically possible to be shaped by conventional foundry due to liquidus temperatures all below 1400°C. According to these same results, the solidus temperatures of all alloys would stay over 1250°C, this suggesting that all alloys would be able to be used under moderate mechanical stresses at temperatures as high as 1200°C. As suggested by calculations, the as-cast microstructures are all dendritic and the interdendritic spaces are occupied by carbides. According to calculations again, the Ni-richest alloys contain chromium carbides, but tantalum carbides are also present, a presence which was not expected. In contrast the Co-richest versions contain only TaC carbides. The DTA experiments show that the solidus and liquidus temperatures both increase by going from the Ni-richest alloys to the Co-richest ones. The TMA experiments demonstrate that the thermal expansions and thermal contractions are rather continuous, without any irregularities, and the average thermal expansion coefficients, all close to 20 × 10-6K-1, do not systematically depend on the respective proportions of nickel and cobalt. This first part of the whole work will be followed by two other parts dealing with the effect of these Ni and Co proportions on the high temperature oxidation phenomena, for temperature variations and for isothermal conditions respectively.